Preparation, Characterisation and Reactivity of Low Oxidation State d-Block Metal Complexes Stabilised by Extremely Bulky Amide Ligands - Hicks, Jamie; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis describes the synthesis and characterization of numerous metal-metal bonded complexes that are stabilized by extremely bulky amide ligands. It provides a comprehensive overview of the field, including discussions on groundbreaking complexes and reactions, before presenting in detail, exciting new findings from the PhD studies. The thesis appeals to researchers, professors and chemistry undergraduates with an interest in inorganic and/or organometallic chemistry.
General Introduction -- Extremely Bulky Amido d-Block Metal(II) Halide Complexes -- Preparation of Low Oxidation State Manganese Complexes Stabilised by Bulky Amide Ligands -- Preparation of Low Oxidation State Group 12 Complexes Stabilised by Bulky Amide Ligands -- Preparation of Low Oxidation State Cobalt Complexes Stabilised by Bulky Amide Ligands -- Preparation of Molybdenum Aminogermylene and Amidogermylyne Complexes -- Appendix.
Keywords: Organometallic chemistry .; Inorganic chemistry; Catalysis; Organometallic Chemistry; Inorganic Chemistry; Catalysis